Knowledge of Emergency Management of Avulsed Teeth Among General Dentists in Kathmandu - Upadhyay, Sumita; Rokaya, D; Upadhyaya, C (Kathmandu University Medical Journal, 2013)
Background An avulsed permanent tooth is one of the most emergency situations in dentistry. Dentists handling the situation should have adequate knowledge in this field. Objective To assess the level of knowledge of emergency management of avulsed teeth among general dentists in Kathmandu. Methods A questionnaire containing 10 close ended questions about emergency management of avulsed teeth was distributed among 102 general dental practitioners working in different private dental hospitals and clinics of Kathmandu. The dental hospital and clinics were randomly selected. This cross sectional study was conducted between January 2012 to February 2012. Results Among the studied group, almost all of the participants, 98(96.1%) said that an avulsed permanent tooth cannot be replanted in all cases. Majority of them, 63 (61.8%) said that the critical time for the replantation is within 20 minutes. General dentists of Kathmandu did not have adequate knowledge about emergency management of avulsed teeth. Conclusion An education program should be conducted to increase the knowledge of general dentists in the management of traumatic injuries to teeth. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 37-40 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7341